DEVELOPING POETRY TEACHING MATERIAL IN ELEMENTARY SCHOOL - Doyin, Mukh (The Journal of Educational Development, 2015)
This study aims to develop poetry teaching materials in accordance with the demands of learning including the demands of the curriculum, student characteristics, and the community in general. The study employed Research and Development (R&D) method in order to create a product in form of childrens poetry criteria as teaching materials in elementary school. The method was simplified so that it only included three main phases, namely (1) a preliminary study, (2) formulation and product development, and (3) validation and dissemination of products. The study results in two outputs, namely the criteria of childrens poetry and model of poetry teaching materials development in elementary school. Childrens poetry criteria expected by the teacher can be seen from three aspects, namely typography, language, and content. Typography involves the writing of title, authorâs name, lines, stanzas, capitalization, the length of poetry, and poetry model. The language used should be beautiful and communicative. The contents of childrens poetry should be useful and can be understood by children. The development of poetry in elementary school teaching materials can be done in three ways: through process of creation, translation, and adaptation. Creation means to create a poem that does not exist before;translation means to shift poetry from the local or foreign languages into Indonesian Language; while adaptation means to create poetry from the existed texts.